The quality of institutions in shaping women's entrepreneurship: A perspective of European Union member states - Aleksandra Gaweł; Timo Toikko (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to investigate the influence of the quality of institutions on women's entrepreneurship from the perspective of European Union (EU) member countries. Quality of institutions is understood as a feature of a well-functioning society and it is considered from four dimensions. Research Design & Methods: Based on the panel data for 27 EU member countries in the years 2009 to 2021, we estimate the model of women's entrepreneurship as a dependent variable and four dimensions of institutional quality as independent variables, namely, quality of public governance, quality of wealth distribution, quality of youth perspectives, and quality based on gender. Findings: The results confirm the mixed effects of institutional quality in shaping women's entrepreneurship. Failures in quality of governance in the aspects of control of corruption, government effectiveness, political stability and absence of violence, and Gini coefficient, can push women into entrepreneurship instead of paid employment as necessity-driven motivators. Aspects of institutional quality such as gender-based political and managerial empowerment, citizens' voices and accountability, and inclusion of younger generations in society act as opportunity-driven enablers of women's entrepreneurship. Implications & Recommendations: The mixed effects of the impact of the quality of institutions on women's entrepreneurship indicate the challenges in combining the goals of reaching well-structured societies and reducing the gender gap in entrepreneurship. To overcome these challenges, policymakers and other stakeholders should focus on opportunity-driven enablers of women's entrepreneurship such as gender-based political and managerial empowerment, citizens' voices and accountability, and inclusion of younger generations in the society. Contribution & Value Added: The novelty of the article lies in the proposed various dimensions of institutional quality: quality of public governance, quality of wealth distribution, quality of youth perspectives, and based on gender. The research results contribute to the theory of entrepreneurship, institutional theory, and gender studies by investigating the impact of various dimensions of quality of institutions on women's entrepreneurship. The mixed explanatory power of institutional quality in shaping women's entrepreneurship is discovered, with respect to both the opportunity-driven enablers and the institutional failures impacting women.
Keywords: L26; J16; O43; 330; women's entrepreneurship; quality of institutions; entrepreneurial enablers; European Union countries